Pengaruh Metode Pembelajaran dan Kemampuan Berpikir Kreatif Terhadap Hasil Belajar Sejarah Siswa di SMA Negeri 5 Depok Kelas 11 IPS - Yusuf Budi Santosa (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2017)
This research has a purpose to determine the extent of the influence fromproblem solvingmethod and the ability to learn think creatively for the outcomes of studyinghistory for students inpublic high school 5 Depok class of 11 IPS. This research is a quantitative research by usingexperimental methods, treatment by level 2x2 design. The instrument used tolearn history is amultiple choice test and for the test for ability to think creatively is questionnaire. 1) The results of themethods showed that the learning outcomes from students who take the history learning withinstructional solving methods (problem solving) higher than students who follow conventionalteaching methods; 2) there are significant interactions between instructional solving method (problemsolving) and the creative thinking ability for students learning outcomes of history; 3) the results ofstudying the history of students who take the learning solving method (problem solving) with creativethinking ability, higher than the historical learning outcomes of students who take conventionalteaching methods with high creative thinking abilities; 4) the results of learning the history ofstudents who take the method of problem solving (problem solving) with creative thinking ability islow, lower than the historical learning outcomes of students who take the instructional conventionalmethods and low creative thinking ability.